A new heat-resistant species of Leiothecium Samson & Mouch. (Eurotiales, Ascomycota) from soil of Argentina - Romero, Stella Maris; Rodriguez Andrade, Ernesto; Romero, Andrea Irene; Amarilla, Leonardo David; Comerio, Ricardo Mario (Muséum National d'Histoire Naturelle (Francia), 2026)
Leiothecium Samson & Mouch. is a genus enclosed into the family Aspergillaceae Link (Eurotiales) including L. ellipsoideum Samson & Mouch. and L. cristatum Y. Marín, Stchigel & Cano, species exhibiting ascospore walls somewhat or irregularly reticulated and prominent crests. During a research on heat-resistant fungi from soil of the semi-arid region of Northern Argentina, several Leiothecium spp. isolates were obtained; morphological and molecular studies were carried out. Phylogenetics showed strong support for the monophyly of the Leiothecium clade and L. ellipsoideum as the sister taxon. Some isolates were identified as Leiothecium ellipsoideum, and a new species provided with reticulate-foveate ascospore ornamentation without prominent crests was described: Leiothecium dictyophorum S.M.Romero & Comerio, sp. nov. Molecular analysis and scanning electron microscopy (SEM) images support the description of L. dictyophorum S.M.Romero & Comerio, sp. nov. as a new species.